ACTIVITY-BASED TEACHING IMPROVES GROSS MOTOR SKILLS AND EARLY ACADEMIC ACHIEVEMENT AMONG NORTH CHENNAI NURSERY STUDENTS: A TEACHER’S PERSPECTIVE - MURUGAN, GAYATHRI; V, RAJASEKARAN; R, AHALYA; NANDAGOPAL, MURUGAN (Innovare Journal of Education, 2020)
Objective: Gross motor skills and cognitive skills are essential prerequisites for the physical development of an early childhood. The World Health Organization (WHO) has developed normal age ranges for the achievement of motor milestones by healthy children. The current study aimed to assess the gross motor skills, cognitive skills related to development achievements and its associated factors among North Chennai nursery students. Materials and Methods: A prospective study was conducted among nursery students from B.V. Victory Nursery and Primary School, Thiruvotriyur, North Chennai, India. Gross motor skills and cognitive skills were assessed through 14 and 13 activities, respectively. The assessment and the scores evaluated as per standard methods and it was recorded and analyzed using Microsoft Excel based tools. Results: Overall, 16 children aged 3–4 years old were included in the study. Of the 16 students, 9 boys and 7 girls were assessed for the gross motor skills and cognitive skills using various activities. From this study, girl’s performance was better than the boy’s performance in various activities. Activities performance and their physical and mental growth were significantly associated with the timely achievement of gross motor and cognitive milestones. Conclusion: This study suggests that students’ gross motor skills and cognitive skills may explore during activity-based teaching module compared to blackboard based study. Hence, we conclude, the activity-based teaching methods for nursery and primary students may help in exploring the student’s potential to the maximum extent with the acquisition of various skills.